Study Of the Effect of Titanium Additions on The Mechanical and Corrosion Properties of AISI 316 Powder Metallurgical Steel - Luz Adriana Cañas Mendoza; Yaneth Pineda-Triana; Lais Mujica Roncery (Ingeniería, 2023)
Context: Powder metallurgy uses metallic and/or non-metallic powders that, through mixing, compacting, and sintering operations, allow obtaining large series of products. In austenitic stainless steels, Cr23C6-type carbides can precipitate at temperatures between 450 and 950 °C. When this occurs, the steel is susceptible to being attacked at its grain boundaries by a phenomenon called sensitization. Titanium is added as a ‘stabilizer’ because it has a greater affinity with carbon for the formation of species at a temperature of approximately 900 ºC, and, during cooling, it consumes the carbon forming MC-type carbides, inhibiting the precipitation of Cr23C6.